International Relations according to Cuneiform Reports from the Tall al-Amarna and Hittite State Archives - Korošeс, V.
Sources — General Characteristics of International Relations of that Period — The Arrangement of Diplomatic Letters: Introduction, Salutations (šulmu), Subject Matter — Brotherhood — Messengers and Gifts: Obligatory Missions, Composition and Juridical Status of Missions — Settling of Conflicts; russ u. engl. Zusammenfassung.